TO THE IRON DEFICIENCY FREQUENCY AMONG URBAN POPULATION PUPILS - Bazarova Minura Usmanovna; Alimova Gulrukh Mukimovna; Gafurova Shaxnoza Mavlyanovna (International Engineering Journal For Research & Development, 2021)
It was studied the iron deficiency frequency state among schoolchildren of the urban population. A sample of urban schoolchildren (12,000) was compiled using the Bradford table. 1200 children at 7-10 ages were examined. (10%).The study results on the iron deficiency identification among schoolchildren of the urban population indicate that among them the latent iron deficiency frequency decreased, and iron deficiency states increased. The latter is especially noticeable in schoolchildren at 11-14 ages and mainly in adolescent girls.